Biomarkery renálních funkcí v prognostické stratifikaci pacientů s akutním koronárním syndromem - Přeček, Jiří; Hutyra, Martin; Kováčik, František; Orság, Jiří; Táborský, Miloš (Cor et Vasa (Brno), 2018)
There is close pathophysiological interaction between the kidneys and the heart, affecting, among others, the risk for development and prognosis of many cardiovascular disease. Early risk stratification of patients with acute coronary syndrome (ACS) is important for optimizing their therapy. Presented is an overview of prognostic stratification of ACS patients according to baseline levels of renal function biomarkers. Apart from classic biomarkers (creatinine, urea) having a dominant role in advanced chronic kidney disease, some novel biomarkers are listed (cystatin C, neutrophil gelatinase-associated lipocalin, interleukin-18) that bring an added value as they are directly associated with the pathological mechanisms of the course of ACS.
Keywords: ledviny; Urea; hodnoty glomerulární filtrace; biologické markery; Acute Kidney Injury; lidé; Prognosis; prognóza; Cystatin C; diferenciální diagnóza; Kidney; Cardio-Renal Syndrome; cystatin C; Risk; Humans; Kidney Diseases; nemoci ledvin; Biomarkers; Lipocalin-2; riziko; lipokalin-2; interleukin-18; akutní poškození ledvin; Acute Coronary Syndrome; močovina; kardiorenální syndrom; kreatinin; Diagnosis, Differential; akutní koronární syndrom; Interleukin-18; Glomerular Filtration Rate; Creatinine